Determination of Father in Artificial Insemination Based on Jurisprudence and Islamic Law - Ezat Sadat Mousavi Dorcheh; Seyed Hamid Jazayeri; Hashem Niazi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The recognition of parentage is one of the important issues in Shari'a, especially in the cases where there is doubt. Artificial insemination between two foreigners is a suspicious example that is criticized in two terms of imperatives and positive rules. Because of independence between imperatives and positive rules, the positive rules of parentage in artificial insemination could be independently criticized.In this regard, the aim of this article is to examine different opinions in the specific evidence of positive rules of parentage regarding the determination of the father, as well as criticizing these views and choosing the right point based on verses and narrations.Based on the result of this paper, the right view is that these children belong to the owner of sperm and other views are rejected because of the invalid reasons. In the end, it can be argued that the privacy, alimony, and inheritance issues can be resolved by considering the real father explained in this article.